2018
DOI: 10.1007/s10608-018-9917-6
|View full text |Cite
|
Sign up to set email alerts
|

Implicit Measures of Actual Versus Ideal Body Image: Relations with Self-Reported Body Dissatisfaction and Dieting Behaviors

Abstract: Body dissatisfaction refers to a negative appreciation of one’s own body stemming from a discrepancy between how one perceives his/her body (actual body image) and how he/she wants it to be (ideal body image). To circumvent the limitations of self-report measures of body image, measures were developed that allow for a distinction between actual and ideal body image at the implicit level. The first goal of the present study was to investigate whether self-reported body dissatisfaction is related to implicit mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 42 publications
2
22
0
1
Order By: Relevance
“…Body image disturbance is related to the body dissatisfaction construct, even if it is less linked to the affective elements and more to the perception feature [14,15]. However, this construct seems more complicated than just the discrepancy between two body sizes [16]. Different elements could be included in the definition of body image disturbance, starting from body perception [17].…”
Section: Introductionmentioning
confidence: 99%
“…Body image disturbance is related to the body dissatisfaction construct, even if it is less linked to the affective elements and more to the perception feature [14,15]. However, this construct seems more complicated than just the discrepancy between two body sizes [16]. Different elements could be included in the definition of body image disturbance, starting from body perception [17].…”
Section: Introductionmentioning
confidence: 99%
“…Muscle dysmorphia (MD) is defined as a type of body dysmorphic disorder (BDD) that is characterized by a preoccupation with a perceived defect in one’s physique that can lead to multiple problems ( Fang & Wilhelm, 2015 ; Foster, Shorter, & Griffiths, 2015 ; Glashouwer, Bennik, de Jong, & Spruyt, 2018 ; Longobardi, Prino, Fabris, & Settanni, 2017 ; Mitchell et al, 2017 ), including the abuse of drugs (particularly anabolic androgenic steroids) ( Davis & Scott-Robertson, 2000 ), prioritizing workout programs over time with family and friends ( Emini & Bond, 2014 ), hiding their body, deterioration in their career ( Celso Alves dos Santos, Patrícia Passarelli, Sergio Carlos, Stephen, & Angélica Medeiros, 2015 ), depression, and even suicide ( Angelakis, Gooding, & Panagioti, 2016 ). Although MD is classified as a BDD, the classification of MD is disputed ( Krebs, de la Cruz, & Mataix-Cols, 2017 ); some researchers have demonstrated that it could be classified as a type of eating disorder ( Murray, Rieger, Touyz, & De la Garza Garcia Lic, 2010 ; Nieuwoudt, Zhou, Coutts, & Booker, 2012 ).…”
mentioning
confidence: 99%
“…Regarding the gender composition of the populations investigated, 57.1% (n=12) of the studies were based on samples composed of university students of both sexes, presenting the results separately and comparatively, and 42.9% (n=9) of the studies were based on samples composed only by female university populations. A large variation in sample size was observed: the smallest sample studied consisted of 67 participants (Glashouwer et al, 2018) and the largest one was composed of 28,703 participants (Vankim et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Development, v. 9, n. 9, e661997513, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i9.7513 10 Inventory (EDI-3). Glashouwer et al (2018) To Research, Society and Development, v. 9, n. 9, e661997513, 2020 (CC BY 4.0 Research, Society and Development, v. 9, n. 9, e661997513, 2020 (CC BY 4.0 de Janeiro.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation